Presleep protein supplementation does not improve recovery during consecutive days of intense endurance training: A randomized controlled trial - Larsen, M. S.; Clausen, D.; Ank Jørgensen, A.; Mikkelsen, U. R.; Hansen, M. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
Recent studies demonstrate that protein ingestion immediately before sleep improves muscle recovery during the night following resistance exercise. Whether this feeding strategy benefits recovery from endurance training has yet to be established. The aim of this study was to investigate the effects of whey protein isolate ingested every night before sleep on subsequent performance and circulatory markers of muscular recovery during a week of intensified endurance training mimicking a training camp. In a parallel design, 32 trained runners underwent a 1-week intervention with a rigorously controlled diet (carbohydrate = 7.2 g·kg-1·day-1, protein = 1.8 g·kg-1·day-1, and fat = 1.0 g·kg-1·day-1) and exercise program (11 sessions) while receiving either a protein (0.5 g·kg-1·day-1) or carbohydrate (0.5 g·kg-1·day-1) beverage every night before sleep. Blood samples were obtained on the morning of Days 1, 4, 7, and 8 and analyzed for markers of muscle damage (creatine kinase, lactate dehydrogenase, and myoglobin). The postintervention 5-km time-trial performance was significantly impaired in both groups (11 ± 24 s, p < .01). Plasma creatine kinase (227% ± 221%, p < .01), lactate dehydrogenase (18% ± 22%, p < .01), and myoglobin (72% ± 62%, p < .01) increased gradually throughout the week with no difference between the groups (p > .05). In conclusion, the presleep protein ingestion did not reduce the decline in performance or ameliorate the rise of circulatory markers of muscle damage during a week of intensified training when compared with the isocaloric carbohydrate ingestion.